FENOMENA CHILDFREE DALAM PERKAWINAN - Muhammad Zainuddin Sunarto; Lutfatul Imamah (IAI Darussalam, 2023)
The order to carry out the marriage has various objectives, which are a stimulus to carry out the marriage immediately. The most well-known purpose of marriage is to complete half of the religion, have fun (wathi'), and have children. Being childfree is an issue that has recently begun to be widely discussed on social media. Childfree is used for couples who do not want to have children or offspring after marriage. For some couples, having children or getting offspring is a big responsibility that will be held accountable in the afterlife, so some couples decide not to have children for reasons of unpreparedness to become parents for reasons of economic, environmental, and physical factors. The notion of childfree is very contrary to the goal in the form of a household that is Sakinah mawaddah warahmah decorated with children in it. The childfree understanding tends to reject Allah's shari'ah which encourages the life of couples and having righteous children, which is indicated by Allah's promises both in the Qur'an verses and the prophet's hadiths. So, it can be understood that this understanding of childfree is contrary to Islamic law and Allah's advice and guidance in running a household. Maintaining offspring or hifdz al-nasl should be done by marrying and having legitimate children